O efeito do autocontrole sobre a influência da comunicação boca a boca eletrônica na decisão do consumidor - Silva, Maízy Cássia (2018)
Aspects about questions related to self-control has received attention within organizational studies, since this factor may have an impact on the consumer’s decision process, both in the traditional environment and in the electronic environment. This term, self-control, refers to the process of a person replacing an initial (desired) response, during the choice process, by a controlled response that suits the context and leads to self-control mechanisms of her actions.Word-of-mouth communication, whether positive or negative, is also a factor that can have an impact on perceptions and consequently on consumer decisions. Consumers tend to value other people' recommendations when they are in the process of decision a purchase, and the online environment has stood out as one of the main ways they use to find information that supports their consumer decisions. The use of the Internet to market products and services can cause changes in the behavior of consumers who tend to become more informed and demanding to carry out their purchases, and may also change the way they relate and convey their opinions, complaints, and consumer experiences. Besides the self-control and word of mouth, another factor that can influence the consumer' purchasing decision process, both in the traditional and electronic environments, is the consumption motivation (hedonic and utilitarian) may also influence the word of mouth. The observation of those two types of motivation may help the efficacy of organizations’ marketing strategies. Therefore, this research intended to analyse the influence of electronic word of mouth communication and of self-control on consumers’ choice process. To answer to this general objective, the following specific objectives were selected: (a) to analyse the effect of electronic word of mouth communication on the purchase intention, on the attitude towards the product, and on the product evaluation; (b) to assess the effect of positive and negative word of mouth communication in different contexts (in the company’s e-commerce site and in social media); (c) verify the effect of self-control on the consumer's decision, in word of mouth communication environments; and (d) to analyse the influence of consumption motivation (hedonic and utilitarian) on the word of mouth. This research’s expected contributions, which also justify it, are grounded on the following aspects: (i) the scarcity of research on positive and negative electronic word of mouth communication in relation to variables such as self-control and consumption motivation; (ii) the understanding of the impact of word of mouth on consumers’ decisions in different consumption contexts; (iii) the managerial and social contributions resulting from the observation of such electronic word of mouth communication; and (iv) the use of the experimental method as a relatively novel procedure in the field of consumer behaviour, which has proved to be increasingly relevant to market phenomenon explanation. To achieve its objectives and contributions, three experimental studies were performed using a survey and quantitative analysis of its replies, applying the t-student, the ANOVA, the chi-squared tests, and the correlation coefficient statistical technique. The first experiment was done in a retail electronic context to verify the influence of word of mouth communication on the consumer’s attitude, evaluation and purchase decision in three sceneries (without commentaries, with positive commentaries and with negative commentaries). Also, a priming was used to identify whether the self-control facet interferes with the relationship between the word of mouth and the consumer’s purchase decision. As a result, the survey yielded 224 valid respondents, and it was noted that the negative word of mouth communication had an influence on the attitude as well as on the evaluation and the purchase intent, however, this was not observed in the case of the positive word of mouth communication. Such results, then, suggest that the negative word of mouth communication may have greater influence on the purchase intention in an online retail context. The analysis show that the presence of self-control resulted in the reduction of the intention to buy in a negative word of mouth environment. After those results, a second experiment was done in a social medium (the Facebook) scenery, yielding a total of 244 valid respondents. Its results pointed towards the influence of the negative word of mouth on two constructs (attitude and product evaluation) while the purchase intent was not influenced. As for the positive commentaries, no influence was observed on the three studied constructs. The results show that self-control caused a reduction in behavioral intention in a negative comment environment. Then, a third experiment was done in another social medium (the WhatsApp), attempting a closer distance between the respondent and the word of mouth communicator. Besides the variables used in the first two experiments, the third study considered the purchase motivation (hedonic and utilitarian). It yielded 561 valid respondents, and results about word of mouth were similar to study 1. The results also show that in the presence and absence of self-control there was a reduction of the behavioral intention in the negative mouth-to-mouth environment, therefore, it should be noted also the impact of the negative comment on the behavioral intention, as well as the motivations of consumption (hedonic and utilitarian). Its findings on the consumption motivation indicated that the hedonic purchase has greater influence on positive word of mouth communication.